2017
DOI: 10.1136/bmj.j5416
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of educational video game versus traditional educational apps at improving physician decision making in trauma triage: randomized controlled trial

Abstract: ObjectiveTo determine whether a behavioral intervention delivered through a video game can improve the appropriateness of trauma triage decisions in the emergency department of non-trauma centers.DesignRandomized clinical trial.SettingOnline intervention in national sample of emergency medicine physicians who make triage decisions at US hospitals.Participants368 emergency medicine physicians primarily working at non-trauma centers. A random sample (n=200) of those with primary outcome data was reassessed at si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 52 publications
3
58
0
3
Order By: Relevance
“…Similar to aviation simulators which train pilots in emergency procedures, serious games have been used to train surgeons in situational awareness for addressing crises and their ability to anticipate nonroutine adverse events during surgery [108A]. Serious games have been used to train forward combat casualty care medical personnel in a hostile remote environment advanced lifesaving procedures and trauma triage to non-trauma specialists [109][110][111].…”
Section: Game-based Learning Health Security Applicationsmentioning
confidence: 99%
“…Similar to aviation simulators which train pilots in emergency procedures, serious games have been used to train surgeons in situational awareness for addressing crises and their ability to anticipate nonroutine adverse events during surgery [108A]. Serious games have been used to train forward combat casualty care medical personnel in a hostile remote environment advanced lifesaving procedures and trauma triage to non-trauma specialists [109][110][111].…”
Section: Game-based Learning Health Security Applicationsmentioning
confidence: 99%
“…The second, Shift: The Next Generation, used analogical reasoning delivered via a puzzle video game. 13,14 Both games included cases of representative and nonrepresentative patients and incorporated mechanisms to provide feedback based on triage decisions.…”
Section: Overview Of Prior Studies and Present Analysismentioning
confidence: 99%
“…The main results from these studies have been previously reported. 13,14 In the current effort, we performed a post hoc secondary analysis by linking physician data from our previous trials to claims records acquired from the Centers for Medicare and Medicaid Services (CMS). The elderly experience high undertriage and mortality after injury, allowing insight into the determinants of variation in triage practices.…”
Section: Overview Of Prior Studies and Present Analysismentioning
confidence: 99%
See 2 more Smart Citations